Предмет:
МатематикаАвтор:
анонимПреобразуем знаменатели дробей: ab - b^2 = (a - b) * b; a^2 + ab = a * (a + b).
a / (b * (a - b)) - b / (a * (a + b)) - 1 / (a + b) + 1 / a = (a^2(a + b) - b^2* (a - b)) / a * b * (a + b) * (a - b) + (-a + a + b)/ a * (a + b) = (a^2(a + b) - b^2* (a - b)) / a * b * (a + b) * (a - b) + b / a * (a + b).
Автор:
camryn8xg1Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть